CRIMINAL LIABILITY OF THE COMPANY'S LEGAL ENTITY IN THE CRIME OF MONEY LAUNDRING - Suluh, Bintang; Farhana, Farhana; Lina Sinaulan, Ramlani (IBLAM LAW REVIEW, 2022)
Based on Law Number 40 of 2007 concerning Limited Liability Companies Jo. Law Number 8 of 2010 Concerning the Prevention and Eradication of Money Laundering Jo. Regulation of the Indonesian Republic of Indonesia Court of Justice Number 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations provides space for criminalizing corporations as subjects who are being held liable for criminal acts of money laundering. However, in practice, law enforcement officers rarely place corporations as subjects for criminal responsibility in money laundering cases, even though corporations play an important role in the occurrence of money laundering crimes. This was proven by the handling of the money laundering case handled by the Corruption Eradication Commission, which for the first time made PT Putra Ramadhan a corporation that was asked to be held responsible for criminal acts of money laundering.